When it comes to financial literacy, is gender really an issue? - S. P. Wagland; S. Taylor (Australasian Accounting, Business and Finance Journal, 2009)
In Australia the introduction of compulsory superannuation has resulted in the financial services industry flourishing and the introduction of numerous new products and services. As a result financial education is critically important to differentiate the extensive range of providers, products and services as means to achieve financial security. Several research papers published since 2000 have attempted to measure the level of financial literacy in today’s society. Some of these studies have suggested that gender is a significant variable impacting on the level of financial literacy. However, to date no such evidence relating to gender difference and its impact on the level of financial literacy is available in Australia. The purpose of this pilot study was to explore the validity of the research outcomes of Chen and Volpe (2002) in an Australian context. To this end the study concentrates on determining the level of financial literacy among Australian undergraduate business students at the University of Western Sydney (UWS).
Keywords: financial planning; gender; financial literacy; Australia; students